Zirconia powder
Patent Information
- Application Number
- JP2026184047
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-17
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-16
Smart Images

Figure 2026169352000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to zirconia powder. [Background technology]
[0002] Zirconia (ZrO2, zirconium dioxide) powder is used as a precursor for sintered or calcined bodies, as well as as an additive. For example, zirconia powder is known to be used in compound applications with electrode active materials and their precursors (hereinafter also referred to as "electrode active materials, etc.") to improve the properties of electrochemical devices (see, for example, Patent Documents 1 and 2).
[0003] In compounding with electrode active materials, the amount of zirconia powder used is extremely small compared to the amount of the electrode active material used. Therefore, high dispersibility is required for the zirconia powder used in compounding with electrode active materials.
[0004] To address these requirements, zirconia-based powder materials that can be easily crushed to produce fine particles are being considered (Patent Document 3). [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] U.S. Publication Application Publication No. 2025 / 079446 Specification [Patent Document 2] European Patent Application Publication No. 4383373 [Patent Document 3] U.S. Publication Application Publication No. 2025 / 042760 Specification [Overview of the Initiative] [Problems that the invention aims to solve]
[0006] The zirconia-based powder material disclosed in Patent Document 3 is said to yield fine particles through an easy crushing treatment, but relatively large and hard aggregated particles remain even after crushing. Such aggregated particles remained in an aggregated state even on the surface of a substance to be composited, such as an electrode active material after compositing. In addition, the zirconia-based powder material disclosed in Patent Document 3 was a powder produced by a neutralization coprecipitation method. Since particle formation occurs instantaneously in the neutralization coprecipitation method, precise condition control is required to control particle formation, and it has been difficult not only to suppress the formation of hard aggregated particles but also to stably produce the zirconia-based powder material itself.
[0007] An object of the present disclosure is to provide at least one of a zirconia powder having higher dispersibility on the surface of a substance to be composited, as compared with conventional zirconia powders used for compositing with an electrode active material or the like, and a method for producing the same. [Means for Solving the Problems]
[0008] In the present disclosure, studies were conducted focusing on the dispersibility of the zirconia powder used for compositing with an electrode active material or the like. As a result, it was found that the surface state of the primary particles constituting the zirconia powder greatly affects the dispersibility during compositing.
[0009] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] A zirconia powder having a pore volume of 0.8 mL / g or less for pores with a pore diameter of 5 nm or more and 6 μm or less, and a BET specific surface area of 22 m 2 / g or more and 120 m 2 / g or less, and a chlorine content of 0.17 mass% or less. [2] The zirconia powder according to the above [1], having a water content of 0.1 mass% or more. [3] The zirconia powder according to any one of the above [1] or [2], having an average particle diameter of 0.60 μm or less. [4] The zirconia powder according to any one of the above [1] to [3], having an average particle diameter of less than 0.20 μm. [5] The zirconia powder according to any one of the above [1] to [4], wherein the ratio of D10 to D90 is 0.35±0.1. [6] The zirconia powder according to any one of the above [1] to [5], wherein the content of the stabilizing element is 0.5 mol% or less. [7] The zirconia powder according to any one of the above [1] to [6], wherein the aluminum content is 0.03 mass% or less. [8] The method for producing a zirconia powder according to any one of the above [1] to [7], comprising: a step of subjecting a zirconia sol obtained by hydrolysis of a zirconium salt solution to a heat treatment at a holding temperature of 760°C or lower to obtain a calcined powder; a step of subjecting the calcined powder to surface modification to obtain a modified powder; and a step of wet-pulverizing the modified powder at 40°C or higher. [9] The production method according to the above [8], wherein the zirconia sol obtained by hydrolysis of the zirconium salt solution is a crystalline zirconia sol.
[10] A composite material comprising the zirconia powder according to any one of the above [1] to [7]. [Effects of the Invention]
[0010] According to the present disclosure, it is possible to provide at least one of a zirconia powder having higher dispersibility on the surface of a material to be composited, as compared with a conventional zirconia powder used for compositing with an electrode active material or the like, and a production method thereof. [Brief Description of the Drawings]
[0011] [Figure 1] Schematic diagram showing the external appearance of zirconia powder particles [Figure 2] Scanning electron microscope observation view showing the dispersibility of Example 3 (scale in the figure is 1 μm) [Figure 3] Scanning electron microscope observation view showing the dispersibility of Comparative Example 1 (scale in the figure is 1 μm) [Figure 4] Scanning electron microscope observation view showing the dispersibility of Comparative Example 2 (scale in the figure is 1 μm) [Modes for Carrying Out the Invention]
[0012] The present disclosure will be described below with reference to an example of an embodiment. Furthermore, the present disclosure includes any combination of the configurations and parameters disclosed herein, as well as any combination of the upper and lower limits of the values disclosed herein. The terms used in this embodiment are as follows.
[0013] "Powder" refers to a composition that is an aggregate of powder particles and also possesses fluidity. "Zirconia powder" refers to a powder whose main component is zirconia, and is essentially a powder made of zirconia. Furthermore, "powder composition" refers to a composition composed of powders with different characteristics, and in particular, a composition containing powders with different compositions.
[0014] "Granular powder" refers to a composition that is an aggregate of powder particles (granular particles) and is fluid, and in particular, a composition in which the powder particles are slowly aggregated. "Zirconia granular powder" refers to a granular powder whose main component is zirconia, and is essentially a granular powder made of zirconia.
[0015] The "main component" is the component that constitutes the main phase (matrix, base material, parent phase) in the composition of the composition, and preferably has a mass percentage of 75% by mass or more, 85% by mass or more, 90% by mass or more, 95% by mass or more, 98% by mass or more, or 99% by mass or more, and is a component that is 100% by mass or less or less by mass.
[0016] "BET specific surface area" is the specific surface area [m²] measured by the BET multi-point method (5 points) using nitrogen as the adsorbent gas, in accordance with JIS R 1626. 2 [ / g] is the BET specific surface area measured under the following conditions. Adsorption medium: N2 Adsorption temperature: -196℃ Pretreatment conditions: Degassing treatment at 250°C for at least 1 hour in an air atmosphere.
[0017] The BET specific surface area can be measured using a common specific surface area measuring apparatus (for example, Tristar II 3020, manufactured by Shimadzu Corporation). The "air atmosphere" refers to an atmosphere mainly composed of nitrogen and oxygen, examples of which include a nitrogen atmosphere having an oxygen concentration of 18 to 23% by volume, and may contain moisture.
[0018] "Pore volume" refers to the pore volume determined from the pore diameter distribution obtained by the mercury intrusion porosimetry, and "pore volume with a pore diameter of D1 or more and less than D2" refers to the total pore volume [mL / g] per 1 g of zirconia powder, which has a pore diameter of D1 [nm or μm] or more and less than D2 [nm or μm], determined from the pore diameter distribution obtained by the mercury intrusion porosimetry. Note that D1 and D2 satisfy the relationship D1<D2. The "pore diameter distribution obtained by the mercury intrusion porosimetry" in the present embodiment is determined by the mercury intrusion porosimetry under the following conditions using a common apparatus (for example, Poremaster GT-60, manufactured by Quantachrome Instruments).
[0019] Measurement range: 0.0036 μm to 10.3 μm Number of measurement points: 120±20 points Mercury contact angle: 140 degrees Mercury surface tension: 480 dyne / cm "D10", "average particle diameter" and "D90" respectively refer to the 10% particle diameter, 50% particle diameter and 90% particle diameter in the volume particle diameter-frequency distribution of the powder measured by a wet method, and are values measured under the following conditions using a common apparatus (for example, MT3300EXII, manufactured by MicrotracBEL Corp.). In the present embodiment, the "average particle diameter" is synonymous with "D50". Measurement method: Laser diffraction method Solvent: 0.02 mass% aqueous sodium hexametaphosphate solution Measurement time: 30 seconds Refractive index of powder: 2.17 Refractive index of solvent: 1.33 Particle shape: Non-spherical Calculation mode: MT3000 mode
[0020] The sample to be measured should be a slurry obtained by dispersing the powder in a 0.02% by mass aqueous solution of sodium hexametaphosphate and removing slow aggregation by dispersion treatment using a homogenizer (e.g., US-150T, manufactured by Nippon Seiki Seisakusho).
[0021] "Moisture content" is a value measured by the change in mass before and after heating and vacuum degassing treatment, and is obtained from equation (1).
[0022] W = {1 - (M2 / M1)} × 100 (1) In the above formula, W is the moisture content [mass%], M1 is the mass of the powder before heating and vacuum degassing [g], and M2 is the mass of the powder after heating and vacuum degassing.
[0023] The heating and vacuum degassing process can be performed by degassing the container holding the powder sample to 250°C and reducing the pressure to 100 mTorr or less using a general rotary pump (e.g., E2M0.7, manufactured by Edwards). The time for the heating and vacuum degassing process should be adjusted as appropriate depending on the volume of powder being processed and the characteristics of the rotary pump, but for example, 90 minutes to 120 minutes is a possible range.
[0024] A "powder X-ray diffraction pattern" is an XRD pattern obtained by smoothing and removing background noise from the XRD pattern of a composition obtained by powder X-ray diffraction (hereinafter also referred to as "XRD") measurement under the following conditions using an analysis program attached to the X-ray diffractometer (for example, the integrated powder X-ray analysis software SmartLab StudioII, manufactured by RIGAKU).
[0025] Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 2° / min Measurement range: 2θ = 26° ~ 33° 2θ = 72°~76° Acceleration voltage / current: 40mA / 40kV Divergence vertical limiting slit: 10mm Divergence / Induction Slit: 1° Light-receiving slit: open Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter Goniometer radius: 185mm XRD measurements can be performed using a standard X-ray diffractometer (e.g., Ultima IV, manufactured by Rigaku Corporation).
[0026] An "XRD peak" is a peak with a peak top at 2θ detected in the XRD pattern obtained in the above-described XRD measurement. In this embodiment, "not having an XRD peak" means that the XRD peak is not detected in the above-described XRD measurement.
[0027] The XRD peaks corresponding to each crystal plane of zirconia are XRD peaks with peak tops at the following 2θ.
[0028] XRD peak corresponding to the monoclinic (111) plane: 2θ = 31 ± 0.5° XRD peak corresponding to the monoclinic (-111) plane: 2θ = 28 ± 0.5° XRD peak corresponding to the tetragonal (101) plane: 2θ = 30 ± 0.5° XRD peak corresponding to the cubic (111) plane: 2θ = 30 ± 0.5° The XRD peaks corresponding to the tetragonal (111) plane and the XRD peaks corresponding to the cubic (111) plane are measured as a single overlapping peak.
[0029] "Monoclinic fraction" is the ratio of the area intensity of the XRD peak of monoclinic zirconia to the total area intensity of the XRD peaks of tetragonal, cubic, and monoclinic zirconia in the XRD pattern obtained in the above-mentioned XRD measurement, and can be calculated from equation (2).
[0030] f m =[I m (111)+I m (-111)] / [I m (111)+I m (-111)+I t (101)+I c (111)] (2) In the above formula, f m is the monoclinic ratio, I t (101) is the areal intensity of the (101) plane of the tetragonal crystal, I c (111) is the areal intensity of the (111) plane of the cubic crystal, I m (111) is the areal intensity of the (111) plane of the monoclinic crystal, I m (-111) is the areal intensity of the (-111) plane of the monoclinic crystal, and I t (111)+I c (111) corresponds to the areal intensity of the XRD peak having a peak top at 2θ=30±0.5°.
[0031] The areal intensity of each XRD peak is a value obtained by analyzing the XRD pattern using an analysis program attached to the X-ray diffractometer (for example, integrated powder X-ray analysis software SmartLab StudioII, manufactured by RIGAKU Corporation). [Zirconia powder] The present embodiment provides a zirconia powder having a pore volume of pores with a pore diameter of 5 nm or more and 6 μm or less of 0.8 mL / g or less, a water content of 2.5 mass% or less, and a BET specific surface area of 22 m 2 / g or more and 120 m 2 / g or less (hereinafter also referred to as "the powder of the present embodiment").
[0032] The powder of the present embodiment is a zirconia powder, that is, a powder containing zirconia as a main component, and may be a powder composed solely of zirconia. The powder of the present embodiment is composed of powder particles. The powder particles include primary particles, which are independent minimum unit particles, and secondary particles, which are particles obtained by physical aggregation of the primary particles. However, in the present embodiment, particles obtained by physical aggregation of secondary particles may be defined as aggregated particles (tertiary particles) to be distinguished from secondary particles in some cases.
[0033] The powder of this embodiment has a pore volume (hereinafter also referred to as "total pore volume") of 0.8 mL / g or less, with a pore diameter of 5 nm to 6 μm. The upper limit of the total pore volume is preferably less than 0.5 mL / g, 0.45 mL / g or less, or 0.4 mL / g or less, and the lower limit is preferably 0.01 mL / g or more, 0.1 mL / g or more, 0.25 mL / g or more, or 0.32 mL / g or more. The total pore volume of the powder of this embodiment can be 0.01 mL / g or more and 0.8 mL / g or less, 0.1 mL / g or more and less than 0.5 mL / g, 0.25 mL / g or more and 0.45 mL / g or less, or 0.32 mL / g or more and 0.4 mL / g or less.
[0034] The powder of this embodiment has a BET specific surface area of 22 m². 2 / g or more 120m 2 It is less than / g. Therefore, the BET specific surface area of the powder in this embodiment is 120 m². 2 / g or less, 100m 2 / g or less, 50m 2 / g or less, 40m 2 / g or less or 35m 2 It is preferable that the amount be less than or equal to / g, and also 23m 2 / g or more, 25m 2 / g or more or 30m 2 It is preferable that it is 1 / g or more. The BET specific surface area of the powder in this embodiment is 20 m². 2 / g or more 120m 2 / g or less, 21m 2 / g or more 100m 2 / g or less, 25m 2 / g or more 50m 2 / g or less, 25m 2 / g or more 40m 2 / g or less, 25m 2 / g or more 35m 2 / g or less, or 30m 2 / g or more 35m 2 One example is that it should be less than or equal to / g.
[0035] One reason why the powder of this embodiment, which possesses both the total pore volume and BET specific surface area described above, exhibits high dispersibility on the surface of the composite material is as follows: Total pore volume is considered one of the indicators that shows the total volume of pores formed between primary particles, between secondary particles, and between aggregated particles (tertiary particles) (hereinafter also referred to as "primary pores," "secondary pores," and "aggregated pores," respectively). On the other hand, BET specific surface area is an indicator that shows the surface state of primary particles, and is considered to represent the sum of the apparent surface of the primary particles (dashed line 11 in Figure 1) and the pore surface present on the surface of the primary particles (10 in Figure 1). By possessing both the total pore volume and BET specific surface area described above, it is considered that the powder particles are composed of primary particles with surface irregularities without excessively containing aggregated pores, which are the main cause of increased pore volume, and the aggregated particles that form them. Furthermore, it is presumed that such surface irregularities are tribochemically modified with atmospheric components such as air, resulting in a reduction in the frictional resistance of the powder particles and improved dispersibility on the surface of the composite. Thus, the powder of this embodiment consists of powder particles composed of primary particles having surface irregularities, and by possessing both the total pore volume and BET specific surface area mentioned above, it is considered that it can also possess a moisture content suitable for dispersion.
[0036] In this embodiment, it is preferable that the powder has a ratio of the total volume of pores with a diameter of 100 nm or more and less than 500 nm, and pores with a diameter of 500 nm or more and less than 6 μm (pores with a diameter of 100 nm or more and less than 6 μm) to the total pore volume (hereinafter also referred to as the "aggregated pore ratio") of 0.45 or less, 0.40 or less, 0.25 or less, or 0.215 or less.
[0037] Pores with a diameter of 5 nm or more and less than 100 nm, pores with a diameter of 100 nm or more and less than 500 nm, and pores with a diameter of 500 nm or more and 6 μm or less correspond to primary pores, secondary pores, and tertiary pores, respectively, and pores with a diameter exceeding 6 μm are considered to correspond to interparticle voids. The powder of this embodiment preferably has few secondary and tertiary pores, and it is considered that the proportion of secondary and tertiary particles in the powder of this embodiment will not hinder dispersibility if the aggregated pore ratio is the value described above. A low aggregated pore ratio is preferable, but examples of aggregated pore ratios for the powder of this embodiment include 0.05 or more, 0.10 or more, or 0.15 or more, and examples include 0.05 or more and 0.45 or less, 0.05 or more and 0.40 or less, 0.10 or more and 0.25 or less, or 0.15 or more and 0.215 or less.
[0038] The powder of this embodiment preferably contains enough moisture to minimize friction with the compounded material. The moisture content of the powder of this embodiment is 2.5% by mass or less, and this moisture content enhances the dispersibility of the powder of this embodiment. The moisture content is preferably 2.3% by mass or less, 2.0% by mass or less, or 1.8% by mass or less. A low moisture content is preferable, but examples include 0.1% by mass or more, 0.5% by mass or more, 1.0% by mass or more, 1.1% by mass or more, 1.3% by mass or more, or 1.5% by mass or more. Examples of moisture content for the powder of this embodiment include 0.1% by mass or more and 2.5% by mass or less, 1.0% by mass or more and 2.5% by mass or less, 1.1% by mass or more and 2.5% by mass or less, 1.3% by mass or more and 2.3% by mass or less, 1.3% by mass or more and 2.0% by mass or less, or 1.5% by mass or more and 1.8% by mass or less.
[0039] The particle size of the powder in this embodiment is one indicator of the dispersion state of the powder particles, and represents the particle size of a state in which at least two or more primary, secondary, and tertiary powder particles are mixed. The particle size of the powder in this embodiment can be any particle size depending on the purpose. Preferred particle sizes include an average particle size (D50) of 0.60 μm or less, less than 0.20 μm, or 0.17 μm or less, and also 0.08 μm or more, 0.10 μm or more, or 0.12 μm or more. For example, 0.08 μm or more and 0.60 μm or less, 0.10 μm or more and less than 0.20 μm, or 0.12 μm or more and 0.17 μm or less.
[0040] The D10 of the powder in this embodiment may be D50 or less, and more preferably less than D50, but is preferably less than 0.20 μm, 0.14 μm or less, or 0.10 μm or less, and is also preferably 0.01 μm or more, or 0.05 μm or more. For example, it may be 0.01 μm or more and less than 0.20 μm, or 0.05 μm or more and 0.14 μm or less.
[0041] The D90 of the powder in this embodiment may be D50 or higher, but is preferably 0.65 μm or less, 0.50 μm or less, or 0.29 μm or less, and also preferably 0.10 μm or more, 0.15 μm or more, or 0.20 μm or more. For example, it may be 0.10 μm or more and 0.65 μm or less, 0.15 μm or more and 0.30 μm or less, or 0.20 μm or more and 0.29 μm or less.
[0042] The powder of this embodiment preferably has uniform particle sizes, i.e., a uniform distribution, and more preferably a monodisperse (monomodal distribution) of particle sizes, and may also have an appropriate distribution width. For example, the ratio of D10 [μm] to D90 [μm] (hereinafter also referred to as the "particle size ratio") may be 0.35 ± 0.1, or more preferably 0.35 ± 0.05.
[0043] The powder of this embodiment may consist solely of zirconia (or even substantially solely of zirconia), but it may also contain components other than zirconia, as long as they do not produce the desired effect.
[0044] In addition to zirconia, the components include at least one of stabilizing elements and additive elements. Stabilizing elements are elements that have the function of stabilizing the crystalline phase of zirconia, and include one or more selected from the group consisting of yttrium (Y), calcium (Ca), magnesium (Mg), and cerium (Ce), and more specifically, yttrium.
[0045] In this embodiment, the content of stabilizing elements in the powder (hereinafter also referred to as "amount of stabilizing elements," and if the stabilizing element is yttrium, also referred to as "amount of yttrium") should be 0 mol% or more, and may contain stabilizing elements, be greater than 0 mol%, or 1 mol% or more, and may also be 25 mol% or less, 10 mol% or less, 5 mol% or less, 25 mol% or less, or 1.5 mol% or less. In this embodiment, the amount of stabilizing elements in the powder may be 0 mol% or more and 10 mol% or less, or greater than 0 mol% and 1.5 mol% or less. In another form of this embodiment, the powder of this embodiment may be substantially free of stabilizing elements (the amount of stabilizing elements is 0 mol%), and examples of such amounts of stabilizing elements may be 0.5 mol% or less, 0.3 mol% or less, 0.1 mol% or less, or 0.05 mol% or less, and may also be 0 mol% or more and 0.5 mol% or less, 0 mol% or more and 0.3 mol% or less, 0 mol% or more and 0.1 mol% or less, or 0 mol% or more and 0.05 mol% or less.
[0046] In this embodiment, the amount of stabilizing elements is the ratio [mol%] of the stabilizing elements in terms of oxides to the total amount of zirconia and the stabilizing elements in terms of oxides.
[0047] The powder of this embodiment may contain additive elements. The additive elements are elements that can impart coloring or other additional functions to zirconia, and include one or more selected from the group consisting of aluminum (Al), silicon (Si), germanium (Ge), lanthanide rare earth elements, and transition metal elements other than zirconium (Zr) and hafnium (Hf). Examples of lanthanide rare earth elements include one or more selected from the group consisting of praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadollium (Gd), terbium (Tb), erbium (Er), and ytterbium (Yb). Furthermore, examples of transition metal elements other than zirconium and hafnium include one or more selected from the group consisting of manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd), and silver (Ag), as well as one or more selected from the group consisting of iron, cobalt, nickel, neodymium, gadolium, terbium, and erbium. Although some lanthanide elements have the function of stabilizing the crystalline phase of zirconia, in this embodiment, for convenience, lanthanide elements may be considered as additive elements.
[0048] Furthermore, the content of additive elements (hereinafter also referred to as "amount of additive elements," and if the additive element is aluminum, also referred to as "aluminum amount") is 0% by mass or more, contains additive elements and is greater than 0% by mass or 0.01% by mass or more, is 0.25% by mass or less or 0.1% by mass or less, and is even more likely to be 0% by mass or more or 0.25% by mass or less, or greater than 0% by mass or less or greater than 0.1% by mass or less. In other forms of this embodiment, it is preferable that the powder of this embodiment substantially does not contain additive elements (the amount of additive elements is 0% by mass), and examples include the amount of additive elements being 0.03% by mass or less, 0.01% by mass or less, or 0.005% by mass or less, and examples include 0% by mass or more or 0.03% by mass or less, 0% by mass or more or 0.01% by mass or less, or 0% by mass or more or 0.005% by mass or less.
[0049] The amount of added elements is the mass ratio [mass%] of the added elements (in oxide equivalent) to the total mass of zirconia and the metal elements (in oxide equivalent).
[0050] In this embodiment, the oxide equivalents of metal elements are, for example, Yttrium as Y2O3, calcium as CaO, magnesium as MgO, cerium as Ce2O3, aluminum as Al2O3, silicon as SiO2, germanium as Ge2O3, praseodymium as Pr2O3, neodymium as Nd2O3, samarium as Sm2O3, europium as Eu2O3, gadollium as Gd2O3, and terbium as Tb7O 11 Erbium should be represented as Er2O3, ytterbium as Yb2O3, manganese as Mn3O4, iron as Fe2O3, cobalt as Co3O4, nickel as NiO, copper as CuO, molybdenum as Mo2O3, technetium as TcO2, ruthenium as Ru2O3, rhodium as Rh2O3, palladium as Pd2O3, and silver as AgO.
[0051] The powder of this embodiment is preferably free of impurities, but may contain impurities as long as it does not impurity. Specific examples of impurities include alkali metal elements, and at least one of sodium (Na) and potassium (K). The powder of this embodiment may also contain hafnia (HfO2), which is an unavoidable impurity of zirconia. In this embodiment, the calculation of compositional values may be performed by treating hafnia as zirconia.
[0052] The powder of this embodiment may contain chlorine. Industrial zirconia powder is manufactured using zirconium chlorides, such as zirconium oxychloride, as raw materials. It is preferable to have a low chlorine content because it helps to suppress the aggregation of primary particles. However, the powder of this embodiment may contain chlorine, and it is preferable that the chlorine content of the powder of this embodiment is 0.25% by mass or less. Even when the powder of this embodiment contains chlorine, it exhibits high dispersibility by satisfying the total pore volume and BET specific surface area described above. The chlorine content is preferably 0.20% by mass or less, 0.17% by mass or less, 0.15% by mass or less, or 0.10% by mass or less. It is preferable that the powder of this embodiment does not contain chlorine, but examples of chlorine content of the powder of this embodiment include 0% by mass or more, greater than 0% by mass or 0.05% by mass or more, and also 0% by mass or more and 0.25% by mass or less, greater than 0% by mass and 0.17% by mass or less, or greater than 0% by mass and 0.10% by mass or less.
[0053] In this embodiment, "chlorine content" is an indicator of the chlorine content contained in the zirconia powder, and is a value [mass%] obtained by X-ray fluorescence analysis using a calibration curve method prepared with a substance whose chlorine concentration is known as a standard substance. X-ray fluorescence analysis can be performed using a general X-ray fluorescence analyzer (for example, ZSM PrimusII A-126, manufactured by Rigaku Corporation).
[0054] A calibration curve can be prepared as follows: First, prepare several reference substances (e.g., zirconia powder containing chlorine) with different chlorine concentrations (e.g., 4±2 points) as standard substances. Next, add 2 mL of silver standard solution (Ag concentration 1 g / L), 3 mL of nitric acid, and 15 mL of hydrofluoric acid to 0.3 ± 0.2 g of each reference substance, stir, and heat at 170°C for 16 hours to dissolve the reference substance. Allow the resulting solution to stand in a cool, dark place for 2 hours. After standing, filter off the precipitated silver chloride (AgCl), and quantify the silver ions contained in the filtrate using an ICP emission spectrometer (e.g., instrument name: Optima 5300 DV, Perkin Elmer). Calculate the amount of silver chloride (AgO) by taking the difference between the amount of silver (Ag) in the quantified silver chloride and the amount of silver (Ag) contained in the silver standard solution. The amount of chlorine contained in the resulting silver chloride is considered to be the amount of chlorine contained in the reference substance. From this calculation result, the chlorine concentration [mass%] of the reference substance can be determined. On the other hand, each reference substance is compressed and molded into pellet-shaped samples, and these samples are measured using an X-ray fluorescence analyzer (e.g., ZSM PrimusII A-126, Rigaku Corporation) to obtain the X-ray fluorescence intensity of each reference substance. The chlorine concentration [mass%] of the reference substances obtained in this way is plotted on the x-axis and the X-ray fluorescence intensity on the y-axis, and an approximate straight line created from each plot so that the correlation coefficient is 0.950 or higher can be used as the calibration curve.
[0055] The powder of this embodiment is preferably a powder mainly containing monoclinic zirconia, and more preferably a powder consisting of monoclinic zirconia. The monoclinic content of the powder of this embodiment is preferably 95% or more or 99% or more, and also preferably 100% or less or less than 100%. The monoclinic content of the powder of this embodiment is 95% or more and 100% or less, or 99% or more and 100% or less. For convenience, the crystalline phase of zirconia in this embodiment may be considered to consist of one or more selected from the group consisting of monoclinic, tetragonal, and cubic crystals. Furthermore, zirconia whose crystalline phase consists of a monoclinic crystal is referred to as monoclinic zirconia, zirconia whose crystalline phase consists of a tetragonal crystal is referred to as tetragonal zirconia, and zirconia whose crystalline phase consists of a cubic crystal is referred to as cubic zirconia.
[0056] The powder of this embodiment can be used in known applications of zirconia powder, but it is preferably used as at least one of an additive and / or a composite material, and more preferably as a composite material. In this embodiment, "compounding" means that a state is maintained in which the other material (the powder of this embodiment) is in contact with or supported on at least one of the surface and / or pores of one of the materials. As a compounding, for example, the powder of this embodiment may adhere to or even partially coat at least a part of the surface of the substrate particles (compounded particles).
[0057] Furthermore, the powder of this embodiment can be used in a composite method. When used as a composite material or composite method, the material to be composited may be, for example, one or more selected from the group consisting of powder, electrode active material, ceramic powder, and polymer material powder, and more specifically, ceramic powder. Since the powder of this embodiment is more easily supported on at least one of the surface and pores of the material to be composited, it is preferable that the material to be composited has a larger average particle diameter than the powder of this embodiment. Preferably, the average particle diameter (D50) of the material to be composited relative to the average particle diameter (D50) of the powder of this embodiment is 5 or more, 10 or more, or 100 or more, and also preferably 500 or less, or 300 or less. Examples include 5 to 500, 10 to 500, or 100 to 300.
[0058] A composite material containing the powder of this embodiment is a material containing the powder of this embodiment and base particles, wherein the base particles have the powder of this embodiment on their surface. Examples of such applications include electrode active materials and, moreover, electrode active materials for secondary batteries.
[0059] Furthermore, the powder of this embodiment can also be used as an additive. For such applications, it can be used as one or more additives selected from the group consisting of fuel cell membranes, ceramic filter membranes, composite membranes, optical membranes, barrier membranes, and medical membranes; further, as one or more additives selected from the group consisting of solid electrolyte fuel cell membranes, microfiltration membranes, limit filtration membranes, gas separation membranes, anti-reflective membranes, high refractive index membranes, corrosion-resistant barriers, oxidation-resistant barrier membranes, and biocompatible membranes; and even further, as an additive to at least one of the electrolyte membrane and separator membrane. [Method for producing zirconia powder] The powder of this embodiment can be produced by any method as long as it satisfies the above-described configuration. However, a preferred method is a method for producing zirconia powder (hereinafter also referred to as "the method of production of this embodiment") which includes the steps of: obtaining calcined powder by heat-treating a zirconia sol obtained by hydrolysis of a zirconium salt solution at a holding temperature of 760°C or lower; obtaining modified powder by surface-modifying the calcined powder; and wet-grinding the modified powder at 40°C or higher.
[0060] In the process of obtaining calcined powder by heat-treating the zirconia sol obtained by hydrolysis of a zirconium salt solution at a holding temperature of 760°C or lower (hereinafter also referred to as the "calcination process"), the zirconia sol obtained by hydrolysis of a zirconium salt solution is heat-treated at a holding temperature of 760°C or lower to obtain calcined powder. In the calcination process, a zirconia sol obtained by hydrolysis of a zirconium salt solution, so-called hydrolysis sol, is provided. Compared to neutralization coprecipitation, hydrolysis proceeds more gently in terms of particle formation, making it easier to control particle formation. Furthermore, while neutralization coprecipitation yields amorphous zirconia sol, the zirconia sol obtained by hydrolysis is crystalline zirconia sol. Therefore, since the zirconia sol obtained by hydrolysis is suitable for stable and repeated production of zirconia powder, the manufacturing method of this embodiment is easily applicable industrially.
[0061] The zirconia sol can be obtained by hydrolysis of a zirconium salt solution, but preferred zirconia sols include those obtained by hydrolysis of a zirconium-containing chloride, and even more specifically, those obtained by hydrolysis of a zirconium oxychloride solution.
[0062] The average particle size of the zirconia sol subjected to the calcination process is 70 nm or more or 80 nm or more, and is preferably 300 nm or less, 150 nm or less, or 120 nm or less, and is 70 nm to 300 nm or 80 nm to 120 nm.
[0063] The zirconia sol used in the calcination process is, for example, a zirconia sol obtained by a manufacturing method disclosed in Japanese Patent Publication No. 2006-240928, Japanese Patent Publication No. 2017-128471, etc.
[0064] The zirconia sol obtained by hydrolysis (hydrolyzed sol) may be zirconia sol that has been washed and dried after hydrolysis. Washing can be done by any method that can remove impurities, for example, washing with water. Drying can be done by any method that removes moisture appropriately, for example, drying in an air atmosphere at a temperature between 80°C and 120°C.
[0065] The heat treatment is performed at a holding temperature of 760°C or lower. If the holding temperature (calcination temperature) exceeds 760°C, the BET specific surface area decreases, the surface irregularities of the primary particles constituting the zirconia powder obtained through the grinding process described later decrease, and the number of aggregated particles increases. As a result, the dispersibility of the obtained powder decreases. The holding temperature is preferably 720°C or lower, 670°C or lower, or 620°C or lower, as the BET specific surface area and total pore volume tend to increase appropriately as the holding temperature decreases within this range. As the holding temperature increases, impurities such as chlorine are more easily removed, and the moisture content tends to decrease. Since impurities contained in the zirconia sol are more easily removed, the holding temperature is preferably 410°C or higher, 460°C or higher, or 510°C or higher, and examples include 410°C to 760°C, 460°C to 720°C, or 510°C to 670°C.
[0066] In the calcination process, the heating rate to the holding temperature is preferably 600°C / hour or less, 300°C / hour or less, or 120°C / hour or less, and preferably 30°C / hour or more, or 80°C / hour or more. By using such heating rates, the zirconia sol is heated more uniformly. Examples of heating rates to the holding temperature include 30°C / hour or more and 600°C / hour or less, or 80°C / hour or more and 120°C / hour or less.
[0067] The atmosphere for heat treatment is preferably an oxidizing atmosphere, and more preferably an atmospheric atmosphere.
[0068] The holding time (calcination time) at the heat treatment holding temperature can be appropriately adjusted according to the amount of zirconia sol used in the calcination process and the characteristics of the heat treatment furnace used for calcination. Examples include 30 minutes or more, 1 hour or more, or 5 hours or more, or 24 hours or less, 15 hours or less, or 10 hours or less, or 30 minutes or more and 24 hours or less, 1 hour or more and 15 hours or less, or 5 hours or more and 10 hours or less.
[0069] In the process of surface-modifying calcined powder to obtain modified powder (hereinafter also referred to as the "modification process"), the calcined powder is surface-modified to obtain modified powder. This suppresses aggregation between powder particles, making it less likely for aggregated particles to form.
[0070] The modification process can be carried out by any means that can suppress the aggregation of powder particles, but it is preferable to bring the calcined powder into contact with an alkaline solution. The alkaline solution can be any solution with a pH of 9 or higher or 10 or higher, and 13.5 or lower or 12.5 or lower, and the pH of the alkaline solution can be said to be 9 or higher and 13.5 or lower, or 10 or higher and 12.5 or lower. In this range, a higher pH facilitates surface modification. An example of a specific alkaline solution is an aqueous ammonia solution (ammonia water).
[0071] The method of contacting the calcined powder with the alkaline solution can be any method that can cause surface modification of the calcined powder, and may include mixing the calcined powder with the alkaline solution or passing the alkaline solution through the calcined powder. Since impurity removal and surface modification are performed simultaneously, the contact method preferably involves passing the alkaline solution through the calcined powder.
[0072] In the step of wet grinding the modified powder at 40°C or higher (hereinafter also referred to as the "grinding step"), the modified powder is wet-ground at 40°C or higher. This yields the powder of this embodiment, which has high dispersibility on the surface of the compounded material. The modified powder is composed of primary particles having surface irregularities. It is presumed that by going through the grinding step, physical aggregation between primary particles is removed while maintaining the surface irregularities of the primary particles, and the surface of the primary particles is further modified.
[0073] In the grinding process, the modified powder is ground by wet grinding. Unlike dry grinding, wet grinding is performed in the presence of a solvent. Therefore, in wet grinding, the grinding proceeds with high dispersibility of the calcined powder, and the calcined powder is easily ground uniformly. Preferred grinding methods include grinding by one or more selected from the group consisting of a vibratory mill, a ball mill, and a bead mill, with ball milling being preferred. Specific grinding methods include using a ball mill with a grinding medium having a diameter of 0.1 mm to 10 mm, and moreover, a diameter of 0.5 mm to 2.5 mm. The grinding medium may be ceramic balls, and moreover, at least one of zirconia balls and alumina balls, and moreover, zirconia balls.
[0074] Wet grinding involves grinding the modified powder in the presence of a solvent. In other words, it grinds the modified powder slurry. To improve grinding efficiency, the mass percentage of modified powder in the modified powder slurry (hereinafter also referred to as "slurry concentration") is preferably 30% by mass or more, or 40% by mass or more, and also preferably 55% by mass or less, or 50% by mass or less. For example, it may be 30% by mass or more and 55% by mass or less, or 40% by mass or more and 50% by mass or less.
[0075] The solvent can be water, or even pure water.
[0076] The grinding temperature is preferably 40°C or higher, more preferably 45°C or higher, and even more preferably 50°C or higher. If the grinding temperature is below 40°C, re-aggregation is likely to occur during grinding, leading to the formation of strong aggregated particles, and the chlorine content tends to increase. Furthermore, moisture is easily incorporated into the resulting zirconia powder, resulting in a decrease in the dispersibility of the resulting zirconia powder. To suppress the volatilization of the solvent during wet grinding, the grinding temperature is preferably 100°C or lower or 80°C or lower, and examples include 40°C to 100°C, 45°C to 80°C, or 50°C to 80°C.
[0077] The grinding time can be adjusted as appropriate depending on the amount of modified powder to be ground and the method of wet grinding, but examples include 15 hours or more or 20 hours or more, 35 hours or less or 30 hours or less, 15 hours or more and 30 hours or 20 hours or more and 30 hours or less.
[0078] The manufacturing method of this embodiment may include a washing step to wash the powder either before or after the grinding step. This makes it possible to reduce impurities remaining after modification (or grinding).
[0079] The cleaning method can be any method that can remove impurities; for example, cleaning with pure water is one such example.
[0080] The manufacturing method of this embodiment may include a sizing step to remove aggregated particles from the powder after grinding. This allows for the removal of coarse particles. The sizing method can be any known method, including dry sizing and sieving. As an example of a sizing method, sieving using a sieve with a mesh size of 150 μm to 200 μm is used. In this case, after sieving, the powder that has passed through the sieve can be collected and used as the powder of this embodiment. [Examples]
[0081] The present disclosure will be described below with reference to examples. However, the present disclosure is not limited to these examples.
[0082] (BET specific surface area) The BET specific surface area was measured using a general specific surface area measuring device (device name: Tristar II 3020, manufactured by Shimadzu Corporation) under the following conditions in accordance with JIS R 1626, using the BET multi-point method (5 points) with nitrogen as the adsorption gas.
[0083] Adsorption medium: N2 Adsorption temperature: -196℃ Pretreatment conditions: Degassing treatment at 250°C for at least 1 hour in an air atmosphere.
[0084] (pore volume) Pore volume was determined from the pore diameter distribution obtained by the mercury intrusion method under the following conditions using a general-purpose instrument (instrument name: Poremaster GT-60, manufactured by Quantachrome). Measurement range: 0.0036 μm to 10.3 μm Number of measurement points: 120 ± 20 points Mercury contact angle: 140degrees Mercury surface tension: 480dyne / cm
[0085] (moisture content) The moisture content was determined from the mass change measured before and after the heating and vacuum degassing treatment, using equation (2) above. The heating and vacuum degassing process was performed by degassing using a general rotary pump (device name: E2M0.7, manufactured by Edwards Corporation) to reduce the pressure of the container holding the powder sample to 250°C and below 100 mTorr.
[0086] (Particle size) D10, average particle size (D50), and D90 were measured using a standard instrument (e.g., MT3300EXII, manufactured by Microtrac-Bell) under the following conditions.
[0087] Measurement method: Laser diffraction method Solvent: 0.02% by mass aqueous solution of sodium hexametaphosphate Measurement time: 30 seconds Refractive index of the powder: 2.17 Refractive index of the solvent: 1.33 Particle shape: non-spherical Calculation mode: MT3000 mode The sample used for measurement was a slurry prepared by dispersing the powder in a 0.02% by mass aqueous solution of sodium hexametaphosphate and removing slow aggregation by dispersion treatment using a homogenizer (e.g., US-150T, manufactured by Nippon Seiki Seisakusho). The particle size ratio was determined from the ratio of D90 to D10 obtained.
[0088] (Chlorine content) The chlorine content [mass%] was determined by X-ray fluorescence analysis using a calibration curve method prepared with three different zirconia powders of known chlorine concentration as standard substances. The X-ray fluorescence analysis was performed using a general X-ray fluorescence analyzer (instrument name: ZSM PrimusII A-126, manufactured by Rigaku Corporation). The calibration curve was prepared according to the method described above. Specifically, zirconia powder containing chlorine and with an unknown chlorine concentration (each standard substance) was mixed with a silver standard solution (Ag 1000, manufactured by Kanto Chemical Co., Ltd.), nitric acid and hydrofluoric acid were added and stirred, and then pressurized acid decomposition was performed by heating at 170°C for 16 hours to dissolve the zirconia, which was then left to stand in a cool, dark place for 2 hours. As a result, the chloride ions and silver ions contained in the powder were reacted, and the precipitated silver chloride was filtered off. The excess silver ions remaining in the filtrate were quantified using ICP (instrument name: Optima 5300 DV, Perkin Elmer). The amount of silver chloride (AgO) was calculated by determining the difference between the amount of silver (Ag) in the quantified silver chloride and the amount of silver (Ag) contained in the silver standard solution, thereby determining the absolute value of the chlorine content in zirconia. A calibration curve was created by plotting the chlorine concentration [mass%] of each standard substance, obtained from the ICP chlorine concentration, on the x-axis and the fluorescence X-ray intensity on the y-axis.
[0089] As the measurement sample, a measurement solution was used which consisted of a mixture of the powder sample, silver standard solution, nitric acid, and hydrofluoric acid, or a solution in which the powder sample was dissolved.
[0090] (Monoclinicity) The monoclinic fraction was determined from the XRD pattern obtained by XRD measurements using a general-purpose X-ray diffractometer (e.g., Ultima IV, Rigaku Corporation) under the following conditions.
[0091] Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 2° / min Measurement range: 2θ = 26° ~ 33° 2θ = 72°~76° Acceleration voltage / current: 40mA / 40kV Divergence vertical limiting slit: 10mm Divergence / Induction Slit: 1° Light-receiving slit: open Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter Goniometer radius: 185mm The monoclinic fraction was determined from equation (2) above.
[0092] The area intensity of each XRD peak was determined by analyzing the XRD pattern using the analysis program included with the X-ray diffractometer (integrated powder X-ray analysis software SmartLab StudioII, manufactured by RIGAKU).
[0093] Example 1 A zirconia sol (crystalline zirconia sol) was obtained by hydrolysis of an aqueous solution of zirconium oxychloride with a zirconium concentration of 0.3 mol / L. The resulting zirconia sol (hydrolyzed sol), with an average sol particle size of 100 nm, was dried in an air atmosphere at 120°C and then crushed in a zirconia mortar.
[0094] The obtained crushed powder was heated in an air atmosphere at a heating rate of 100°C / hour to a holding temperature of 500°C, and then calcined at this holding temperature (calcination temperature) for 2 hours. The powder after calcination (calcined powder) had a BET specific surface area of 28 m². 2 The zirconia powder had a density of 1 / g and a monoclinic content of 100%, and consisted of monoclinic zirconia.
[0095] Surface modification was performed by passing an ammonia aqueous solution with a pH of 12±1 through the calcined powder. After passing the ammonia aqueous solution through the powder, the resulting modified powder was washed with pure water.
[0096] The modified powder and pure water were mixed to prepare a modified powder slurry with a slurry concentration of 45% by mass. Dilute hydrochloric acid was added to the slurry so that the pH of the slurry was 5.75 ± 0.75. Then, while maintaining the temperature at 60°C, the slurry was wet-milled using a ball mill with 2 mm diameter zirconia balls as the grinding medium. The slurry was then heated in an air atmosphere at a heating rate of 3°C / min to a holding temperature of 120°C and dried at this holding temperature for 20 hours.
[0097] The dried powder (dried powder) was ground in a zirconia mortar and then passed through a sieve with a mesh size of 182 μm to obtain the zirconia powder of this example, which consists of zirconia.
[0098] Example 2 The zirconia powder of this example was obtained using the same method as in Example 1, except that the holding temperature during calcination was set to 600°C.
[0099] Example 3 The zirconia powder of this example was obtained in the same manner as in Example 1, except that the holding temperature during calcination was set to 615°C.
[0100] Example 4 The zirconia powder of this example was obtained in the same manner as in Example 1, except that the holding temperature during calcination was set to 640°C.
[0101] Example 5 The zirconia powder of this example was obtained using the same method as in Example 1, except that the holding temperature during calcination was set to 700°C.
[0102] Example 6 The zirconia powder of this example was obtained in the same manner as in Example 1, except that wet grinding was performed at 50°C.
[0103] Comparative Example 1 The zirconia powder of this comparative example was obtained using the same method as in Example 1, except that the holding temperature during calcination was set to 800°C.
[0104] Comparative Example 2 The zirconia powder of this comparative example was obtained in the same manner as in Example 1, except that wet grinding was performed at room temperature (20-25°C).
[0105] The results are shown in the table below.
[0106] [Table 1]
[0107] Examples 1 to 6 and Comparative Example 1 showed that while the BET specific surface area, total pore volume, and moisture content tended to decrease with increasing calcination holding temperature, all samples maintained a similar average particle size. Furthermore, while the chlorine content tended to decrease with increasing calcination holding temperature, the decrease in chlorine content was less significant above 600°C. In addition, Comparative Example 2, which used a lower wet grinding temperature compared to Example 1, showed a higher chlorine content in the resulting powder.
[0108] <Assessment of mixing properties / Assessment of dispersion properties> As the material to be composited, alumina (Al2O3) powder with an average particle size (D50) of 3 μm was used, and it was dry-mixed with the zirconia powder of each example or comparative example so that the mass ratio of the zirconia powder was 10% by mass.
[0109] The results are shown in the table below. In the table, "◎" indicates particles dispersed on the surface of alumina particles with no aggregated particles observed, "〇" indicates particles dispersed on the surface of alumina particles with aggregated particles observed, and "×" indicates aggregates of independent zirconia particles observed. D50 / D50 represents the average particle size (D50) [μm] of the composite material relative to the average particle size (D50) [μm] of the powder in this embodiment.
[0110] [Table 2]
[0111] BET specific surface area is 22m² 2The powder of Comparative Example 1, which had a moisture content of less than 2.5% by mass, and the powder of Comparative Example 2, which had a moisture content exceeding 2.5% by mass, both exhibited low dispersibility and formed aggregated particles on the surface of the alumina particles. Figures 2 and 3 show SEM observations of Example 3 and Comparative Example 1 after compounding. From Figure 2, it can be confirmed that zirconia powder particles with a particle size of 0.5 μm or less are dispersed on the alumina particles. On the other hand, from Figure 3, in addition to zirconia powder particles with a particle size of 0.5 μm or less, zirconia powder particles with a particle size of approximately 1 μm were observed, confirming that aggregation of zirconia powder particles had occurred. Furthermore, from Figure 4, it can be confirmed that aggregated zirconia powder particles with a particle size of 0.3 μm were present on the alumina particles. From this, it was confirmed that the zirconia powders of the examples had high dispersibility and were suitable for compounding, and even for compounding with the materials to be compounded. [Explanation of Symbols]
[0112] 100 primary particles 10 Surface pores 11. Apparent surface
Claims
1. The pore volume is 0.8 mL / g or less, with a pore diameter of 5 nm to 6 μm, and the BET specific surface area is 22 m². 2 / g or more 120m 2 Zirconia powder characterized by having a concentration of 0.17% by mass or less per gram and a chlorine content of 0.17% by mass or less.
2. The zirconia powder according to claim 1, wherein the moisture content is 0.1% by mass or more.
3. The zirconia powder according to claim 1 or 2, wherein the average particle size is 0.60 μm or less.
4. The zirconia powder according to claim 1 or 2, wherein the average particle size is less than 0.20 μm.
5. The zirconia powder according to claim 1 or 2, wherein the ratio of D10 to D90 is 0.35 ± 0.
1.
6. The zirconia powder according to claim 1 or 2, wherein the content of stabilizing elements is 0.5 mol% or less.
7. The zirconia powder according to claim 1 or 2, wherein the aluminum content is 0.03% by mass or less.
8. A method for producing zirconia powder according to claim 1 or 2, comprising the steps of: heat-treating a zirconia sol obtained by hydrolysis of a zirconium salt solution at a holding temperature of 760°C or lower to obtain calcined powder; surface-modifying the calcined powder to obtain modified powder; and wet-grinding the modified powder at 40°C or higher.
9. The manufacturing method according to claim 8, wherein the zirconia sol obtained by hydrolysis of the zirconium salt solution is a crystalline zirconia sol.
10. A composite material comprising zirconia powder according to claim 1 or 2.
Citation Information
Patent Citations
Multilayer annular hole nickel-cobalt-aluminum precursor, preparation method for precursor and positive electrode material
EP4383373A1
Zirconia-based powder material
US20250042760A1
Multilayer Annular Pore Nickel-Cobalt-Aluminum Precursor And Preparation Method And Positive Electrode Material Thereof
US20250079446A1